Forest: a Component of Farming Systems in Himachal Pradesh - Singh, D. V. (Indian Forester, 1996)
Forests are as integral a part of fanning system as arable land and livestock. Thus, crop production, animal husbandry and forestry constitute the three main closely and inseparably integrated component in hill farming system. Forests are more closely linked with livestock as compare to other component of the mountain farning system. The number of livestock kept per household in hills is mainly determined by the available forest and grazing land in the area. Forest provides feed and bedding material to the livestock and these inputs constitute 49 per cent of total cost of production. Similarly forests contributes 19,20 and 26 per cent in total cost of production of foodgrain, fruits and vegetable, respectively. Besides these contributions, forests fulfils more than 90 per cent domestic energy requirement of hill people and out of which public forests accounts for 50 per cent of total requirement. An attempt has been made in this paper to assess the contribution of forest in farming systcm of the State.